2012
DOI: 10.1103/physrevlett.109.237001
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the Meissner-Ochsenfeld Effect and the Absence of the Meissner State in UCoGe

Abstract: We present low field magnetization and susceptibility measurements made on a single crystal of the ferromagnetic superconductor UCoGe. The interplay between ferromagnetism and superconductivity comes into view in the study of hysteresis along the c axis (easy magnetization axis). The Meissner state (perfect diamagnetism) could not be observed in very low magnetic fields for all three crystallographic directions, implying that the sample is always in the mixed state. Notwithstanding, the Meissner-Ochsenfeld eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 20 publications
1
48
0
Order By: Relevance
“…According to the experimental results reported in [16][17][18] this field at ambient pressure is larger than the lower critical field field H c1 in UCoGe. So, the complete field screening is not realised, and the phase transition occurs directly to the superconducting mixed state.…”
Section: Magnetostaticsmentioning
confidence: 81%
“…According to the experimental results reported in [16][17][18] this field at ambient pressure is larger than the lower critical field field H c1 in UCoGe. So, the complete field screening is not realised, and the phase transition occurs directly to the superconducting mixed state.…”
Section: Magnetostaticsmentioning
confidence: 81%
“…On experiments [7] in UCoGe the diamagnetic response was observed and this may be explained by the strong vortex pinning -the vortex configuration is frozen and only the surface Meissner current contributes to the screening.…”
Section: Discussionmentioning
confidence: 97%
“…In real FS compounds these pinning effects may be, of course, rather strong. For example, the recent magnetization measurements in U CoGe [7] show an important vortex pinning effect, overcoming the magnetic domain pinning. The interplay between these two types of pinning makes the physics of the domain structure in FS very reach.…”
Section: Introductionmentioning
confidence: 99%
“…Imaging at the base temperature of 0.2 K was achieved for the study of the ferromagnetic superconductor UCoGe [25] . We showed that by controlling the shape of the very end of the MicroSQUID-tip we can reduce the MicroSQIUID-sample distance to at least 420 nm while scanning reliably, opening the path to the precise determination of the penetration depth in superconductors.…”
Section: Discussionmentioning
confidence: 99%